2016
DOI: 10.6018/turismo.38.271351
|View full text |Cite
|
Sign up to set email alerts
|

Fiabilidad de las críticas hoteleras autenticadas y no autenticadas: El caso de TripAdvisor y Booking.com

Abstract: RESUMENEl presente estudio analiza el Electronic Word Of Mouth (eWOM) en el sector turístico a través de TripAdvisor y Booking.com. Este trabajo pretende comprobar si las críticas sobre la falta de veracidad de los comentarios de TripAdvisor están fundamentadas, comparando los rankings de hoteles en cinco ciudades españolas con los del portal de reservas Booking.com.Los resultados revelan que existe una correlación entre ambos rankings, indicando así que la falsificación y la manipulación de opiniones en TripA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
0
17
0
5
Order By: Relevance
“…TripAdvisor is one of the most influential eWOM sources in the hospitality and tourism context (Yen and Tang, 2015) not only does it supply a source of information for travellers, but also its data allows researchers to obtain useful information focusing on User-Generated Content (UGC) through the online travel reviews posted by consumers (Ayeh, Au and Law, 2013;Balagué, Martin-Fuentes and Gómez, 2016;Liu, Pennington-Gray, Donohoe and Omodior, 2015;Melián-González, Bulchand-Gidumal and González López-Valcárcel, 2013) and has been the most frequently studied platform in the last five years (Chen and Law, 2016).…”
Section: Word Of Mouthmentioning
confidence: 99%
“…TripAdvisor is one of the most influential eWOM sources in the hospitality and tourism context (Yen and Tang, 2015) not only does it supply a source of information for travellers, but also its data allows researchers to obtain useful information focusing on User-Generated Content (UGC) through the online travel reviews posted by consumers (Ayeh, Au and Law, 2013;Balagué, Martin-Fuentes and Gómez, 2016;Liu, Pennington-Gray, Donohoe and Omodior, 2015;Melián-González, Bulchand-Gidumal and González López-Valcárcel, 2013) and has been the most frequently studied platform in the last five years (Chen and Law, 2016).…”
Section: Word Of Mouthmentioning
confidence: 99%
“…This article tries to fill this gap and helps incorporate research with the validity of reviews posted without verification procedures. Moreover, this article tries to provide additional insight into ANALYSIS OF HOTEL ONLINE REVIEWS 3 Booking.com are a popular online source for hotel information, as are social media websites like Trip Advisor and Facebook (Sun, Fong, Law & Luk, 2015), which draw the attention of researchers (Balagué, Martin-Fuentes, & Gómez, 2016;Viglia, Minazzi, & Buhalis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the fear that user-generated contents can be jeopardized by fake comments made under the cover of anonymity, O'Connor (2010) argues that such fear is baseless since research has found little evidence of fake reviews, only residual cases. Also, a high number of reviews are a sign of credibility, since it diminishes the manipulative impact of any fake reviews (Ong, 2012;Balagué et al, 2016). For this reason, many online intermediaries -including TripAdvisor -require reviewers to register and provide some additional personal information including name, residence, nationality or gender (Jeong & Jeon, 2008;Xie, Miao, Kuo & Lee, 2011).…”
Section: Ewom In the Tourism And Hospitality Industrymentioning
confidence: 99%
“…A large group of papers, albeit mainly focused on hotels, used TripAdvisor or other sites as a source of data, collecting the data either manually or automatically (e.g., Gerdes & Stringam, 2008;Jeong & Jeon, 2008;Ye et al, 2009;Melián-González, Bulchand-Gidumal & López-Valcárcel, 2013;Limberger et al, 2014, Balagué et al, 2016Pacheco, 2017, among others). For instance, Ye et al (2009) empirically investigated the impact of online consumer-generated reviews on hotel room sales, by tallying the number of reviews received on a travel website which they consider to be a proxy of room sales.…”
Section: Analysis Of Online Reviews In the Hospitality Industrymentioning
confidence: 99%
See 1 more Smart Citation